Current Gastrointestinal Imaging in Children - Jogeesvaran, Haran; Elsayad, Mohamed; Kirupananthan, Ramiya (Current Pediatric Reviews, 2015)
Gastrointestinal (GI) pathologies in children present with overlapping symptoms and signs. Radiological imaging is assuming a more prominent role in the diagnostic pathway. This article is aimed primarily at paediatricians, helping them to understand and thereby better utilise radiological imaging. The strengths and weaknesses of the various imaging modalities are outlined in a concise manner. Illustrative conditions are discussed with an emphasis on key diagnostic features along with several, high quality annotated images. Emerging concepts are introduced throughout the article. These are referenced by the latest research to give the reader an update of current GI imaging in children.
Keywords: pediatric radiology